Africanising the Curriculum Indigenous Perspectives and Theories - Msilaÿ, Vuyisile (African Sun Media, 2016)
The alienating nature of the dominant curriculum in African schools and universities is an issue which simmered just below the surface in the 2015 student protests that swept through the South African higher education sector. The collection of essays found in this timely publication, offers compelling arguments for the deliberate embrace of the African culture to advance African knowledge and enhance African lives. It proposes fresh perspectives on what shape and form a decolonised curriculum should take on.